A network model to assess base-filter combinations. (April 2017) - Shire, T.; O'Sullivan, C.
Abstract: Granular filters retain base material within the narrowest constrictions of their void network. A direct comparison of the base material particle size distribution (PSD) and the filter constriction size distribution (CSD) cannot easily be used to assess filter-base compatibility. Here a conceptually simple random-walk network model using a filter CSD derived from discrete element modelling and base PSD is used to assess filter-base compatibility. Following verification using experimental data the model is applied to assess empirical ratios between filter and base characteristic diameters. The effects of filter density, void connectivity and blocking in the first few filter layers are highlighted.